2012
DOI: 10.1134/s1063783412070074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-temperature treatment and subsequent high-temperature annealing on the critical current density of YBa2Cu3O y

Abstract: The field dependences of the critical current density of the HTSC compound YBa 2 Cu 3 O y recov ered at T = 920-950°C after the low temperature treatment have been investigated. At T = 200°C, structural defects are formed in a wet environment, which are capable of initiating pinning of magnetic vortices. A short term (1-3 h) recovery annealing performed at T = 930-950°C leaves in the samples a fairly large amount of structural defects formed during the low temperature treatment, which results in a substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, after the double heat treat ment, depending on field, the critical current density increases as compared to that for samples prepared by the traditional ceramic technology [15] is observed. The cause for improvement is the retention of a por tion of stacking faults formed in the course of low temperature annealing.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, after the double heat treat ment, depending on field, the critical current density increases as compared to that for samples prepared by the traditional ceramic technology [15] is observed. The cause for improvement is the retention of a por tion of stacking faults formed in the course of low temperature annealing.…”
Section: Introductionmentioning
confidence: 89%
“…We simulate the metal sphere using two-component homogeneous solid environment consisting of two continuous continuums: the conduction electrons and lattice ions, for which carried out the hypothesis of continuity and local thermodynamic equilibrium [2,3].…”
Section: Research Objectmentioning
confidence: 99%
“…To describe mechanoelectric distributions in the sphere we consider two pairs of parameters of the thermodynamic state : a) for redistribution of electrical charges -concentration of electrons Ce, ions Cion and the chemical potentials Me, Mion corresponding them (concentrations are dimensionless, dimension of chemical potentials -J/kg); b) for the stressed state -tensors of deformation ê and mechanical stresses  [2][3][4][5].…”
Section: Selecting State Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12], it was found that, during the treatment of highly-textured YBa 2 Cu 3 O 6.8 ceramics, packets of 124-type planar stacking faults are formed. In [14][15][16], it was shown that such defects are pinning centers favoring a substantial increase in the critical current density, especially in magnetic fields applied perpendicularly to the axis c.…”
Section: Introductionmentioning
confidence: 99%